Stolen song - Zingesser, Eliza (Cornell University Press, 2020)
Of birds and madmen : Occitan songs in French songbooks – Keeping up with the French : Jean Renart's francophile empire in the Roman de la rose – Birdsong and the edges of the empire : Gerbert de Montreuil's Roman de la violette – From beak to quill : troubadour lyric in Richard de Fournival's Bestiaire d'amour – The rustic troubadours : Occitanizing lyrics in France
Enthält ein Literaturverzeichnis auf Seite 213-229
Keywords: Troubadour songs; Literature; Medieval; Poetry; Medieval; Provençal poetry; French literature; Troubadours; Quotations in literature